Analysis of the Influence of Business Development Services (BDS) on The Profitability of Small and Medium Enterprises (SMEs) in Distro in Medan Area - Sri Murniyanti; Nova Azahra; Muhammad Rizaldy Wibowo (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study explores the impact of Business Development Services (BDS) on the profitability of small and medium enterprises (SMEs), with a specific focus on distro businesses in the Medan Area, Medan. BDS refers to a range of non-financial services aimed at enhancing the growth, capacity, and performance of businesses. These services may include training, mentoring, market access, business planning, and other forms of support. The core objective of this research is to determine whether the utilization of BDS has a measurable influence on the financial outcomes of SMEs, particularly in terms of profitability. The study employs a quantitative research approach using a survey method. Data was collected through questionnaires distributed to selected owners of distro businesses who had previously accessed BDS programs. The analysis was conducted using simple linear regression to evaluate the relationship between BDS engagement and business profitability. The results reveal a statistically significant and positive influence of BDS on profitability. SMEs that actively engaged with BDS programs showed noticeable improvements in their financial performance, indicating the effectiveness of these services in supporting business growth. In particular, distro businesses that received BDS assistance experienced increased efficiency, improved market reach, and better management practices, which contributed to higher profit margins. Based on these findings, the study highlights the critical role that BDS can play in enhancing the sustainability and competitiveness of SMEs. It recommends that more business owners in the distro sector take advantage of available BDS programs to support their development. Furthermore, it underscores the importance of governmental and institutional support in promoting and expanding access to BDS to ensure that a wider range of SMEs can benefit from these valuable services.